Physicochemical Characteristics of Canned Sayur Lilin (Saccharum edule) as a Traditional Food of North Maluku - Rasulu, Hamidin; Wulansari, Angela; B. Talebe, Yusnaini; Juharni, Juharni; M. Mustafa, Ikrima (Agrikan Jurnal Agribisnis Perikanan, 2022)
The purpose of the study is the development of traditional food in North Maluku by studying the physicochemical characteristics of ready-to-eat canned candle vegetables and optimizing processed products that are canned by meeting quality standards, especially nutritional information. The implementation method is the optimization and characterization of canned wax vegetables with 2 different varieties, namely orange sayur lilin (SLO). As a result that optimization on 2 varieties of canned sayur lilin did not have significant differences with physical properties in the color of each L* (65.90-66.03), a+ (45.23-48.43), and b+ (38.25-39.05). Chemical properties include total energy 53.06-54.12 kcal/100g, total fat 2.98-3.01%, protein 1.70-1.75%, carbohydrates 4.86-4.99%, water content 88.96-88.99% and ash content 1.50-1.62%. In conclusion that the traditional food canning of wax vegetables with two different varieties provides product quality information the product affected by the properties of the material that is easily mushy due to the presence of heat and also stirring makes the product easily destroyed, but does not damage the chemical components of the final product.